The slope of this problem is 0, since y = mx +b. m is the slope. First move all like terms to one side y-9 = 17, so y = 26. In the y = mx+b form y = 0x + 26, since there are zero xs. So the slope is 0.
The slope of this problem is 0, since y = mx +b. m is the slope. First move all like terms to one side y-9 = 17, so y = 26. In the y = mx+b form y = 0x + 26, since there are zero xs. So the slope is 0.
1. Parentheses 2. Exponents 3. Multiplication or Division (right to left) 4. Addition or subtraction (right to left) is the order of operations, so 4*6 which equals 24 which is done before 36-4 (multiplication before subtraction), so actually it is 36-24 = 12. Where is the exponent...
Everthing said by the other posters here is correct with one addition just as x cannot equal 4, x cannot equal -4, because the original denominator was (x-4)(x+4), and neither factor can equal 0. x-4 = 0, x=4, x+4 = 0, x=-4. There is a little jump or a circle on the graph...
actually it's put in lowest terms. You find the GCF (greatest common factor) of the numerator and denominator, the highest number that divides without a remainder into each. Here it is 6. 18/6 is 3, and 48/6 is 8, so the answer is 3/8.
The first thing to remember in this table is that the domain is the set of xs and the range is the set of ys or f(x)s. First you should check and see if there is a constant slope for this table. For each 1 in the domain I see the range increases 6. So the slope is constant and...
Just remember when there is no number or coefficient before a variable it is understood to be 1. So 2x + x is actually 2x + 1x which equals 3x. If you have trouble remembering that I just suggest anytime you see a variable without a coefficient write in a "1" where...
when using the distributive property you have to remember to distribute the -7, so -7(n-1) = -7*n + -7*-1, so it actually equals -7n+7 not -7n + 1, so if the equation were -7n + 7 = 0 then the next step would be to subtract 7 from both sides in order to isolate the variabe...
If there were a second equation, you would isolate y in this equation and solve the 2nd equation for what x equals. Here -3x+y=-2, so move everything but the y over to the other side. So add 3x to both sides to isolate the y, -3x + 3x + y = -2+3x, so...